Implementasi Pendidikan Inklusi dalam Mengembangkan Karakter Cinta Tanah Air di TK Laboratory Pedagogia Bantul Yogyakarta - Asiah, Asiah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to describ how the implementation of inclusve education in developing thecharacter of patriotism in the pedagogia kindergarten Bantul yogyakata. This research usesdescriptive qualitative method, with research subjects involving 12 grup B children,class teachers in Pedagogia Bantul Kindergarten. While the method of data collection uses the method of observation, interviews and documentation. As for the stages in data collection using data reduction, data presentation, and drawing conclusions of verification. The results of research on the implementation of inclusive education in developing the character of homeland love in kindergarden Bantul conducted in the learning process both inside and outside the room. Through inclusive education children have been able to develop the character of patriotism, it can be seen with children who have been able to practice ceremonies, memorize national pancasila and its symbols, know Indonesia culture, especially the culture around where children live. As for the supporting and inhibiting factors in the implementation of inclusive education in developing the character of a motherland of love, namely teachers, parents, facilities and infrastructure as well as the environment